Implementasi Customer Relationship Management Digital pada Sektor Jasa Kebersihan Menggunakan Metode Waterfall - Denny Fadilah; Muhammad Patria (Arcitech: Journal of Computer Science and Artificial Intelligence, 2025)
The customer complaint management system in cleaning service companies still relies heavily on manual processes, while previous studies have focused more on the implementation of general CRM without focusing on structured ticketing mechanisms and system usability evaluation. This study aims to design and implement a web-based Customer Relationship Management system in the cleaning services sector using the Waterfall method, with an emphasis on single ticket ownership, clear resolution flows, and usability evaluation. The research uses a mixed method approach through observation, interviews, and documentation studies, as well as system testing using User Acceptance Test and System Usability Scale. The SUS test involved 15 respondents and produced an average score of 75.83, which is in the good category, indicating an adequate level of system usability. The UAT results show that all the main functions of the system run according to user operational needs. This research provides practical contributions in the form of a measurable CRM ticketing implementation model for cleaning service companies and academic contributions through empirical evidence of Waterfall-based CRM usability in the context of cleaning services.